EFEKTIVITAS PENGGUNAAN BUKU CERITA DIGITAL TERHADAP PENGUASAAN KOSAKATA DAN KEMAMPUAN PEMAHAMAN MEMBACA SISWA KELAS V DI MIN 1 OGAN ILIR - Risdatul Isnaini; Masagus Firdaus; Mulyadi Mulyadi (EDUPEDIA, 2026)
This classroom action research aimed to improve fifth-grade students’ vocabulary mastery and reading comprehension through the use of digital storybooks. The study was conducted at MIN 1 Ogan Ilir and involved 20 students in the 2024/2025 academic year. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through vocabulary and reading comprehension tests, observation sheets, and interviews. The findings revealed a significant improvement in students’ learning outcomes and classroom participation. In Cycle I, 55% of students achieved the Minimum Mastery Criterion (KKM), with an average score of 73.25. After revising the instructional strategy and implementing improvements in Cycle II, 85% of students successfully met the KKM, and the class average increased substantially. Observation results also indicated a positive shift in students’ engagement, enthusiasm, and interaction during learning activities. The integration of digital storybooks created a more interactive and meaningful learning environment by combining text, audio, and visual elements. Therefore, digital storybooks proved to be an effective instructional medium for enhancing vocabulary mastery and reading comprehension among elementary school students